2016
DOI: 10.1016/j.jpowsour.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Gas-diffusion-layer structural properties under compression via X-ray tomography

Abstract: There is a need to understand the structure properties of gas-diffusion layers (GDLs) in order to optimize their performance in various electrochemical devices. This information is important for mathematical modelers, experimentalists, and designers. In this article, a comprehensive study of a large set of commercially available GDLs' porosity, tortuosity, and pore-size distribution under varying compression is presented in a single study using X-ray computed tomography (CT), which allows for a noninvasive mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
193
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(217 citation statements)
references
References 71 publications
19
193
1
4
Order By: Relevance
“…The size distributions shown in Fig. 13 are in good agreement with accepted values for similar materials [59][60][61][62].…”
Section: Fibrous Mediasupporting
confidence: 84%
“…The size distributions shown in Fig. 13 are in good agreement with accepted values for similar materials [59][60][61][62].…”
Section: Fibrous Mediasupporting
confidence: 84%
“…15,17,18,[20][21][22][23][24] While such reports represent excellent engineering efforts to improve RFB power density, increases in mass transfer rates are rarely quantified, arguably due to insufficient knowledge of relevant transport processes within the specific electrode material. 14 The porous electrodes used for RFBs are typically comprised of loose cylindrical fiber beds where the porosity is ∌ 70-90%, 25 but prior electrochemical modeling efforts have described the mass transport rates in RFBs as a function of either mass transfer coefficients for packed bed reactors 18,26 or Bruggemancorrected diffusion coefficients. 27 Additionally, recent reports have suggested that flow rate dependent reactor performance improvements vary for different flow field types.…”
mentioning
confidence: 99%
“…For comparison the pore sizes in SGL 25AA and Toray 090 are typically greater than 30 microns. 49 Permeability coefficient.-In-plane permeability as a function of compression was measured before and after carbonization. As expected, permeability decreased with increasing compression, since porosity and open space for flow is reduced.…”
mentioning
confidence: 99%